2015
DOI: 10.1111/ejh.12546
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitors and IMiDs can overcome some high‐risk cytogenetics in multiple myeloma but not gain 1q21

Abstract: Chromosomal aberrations have significant prognostic importance in multiple myeloma (MM). However, proteasome inhibitors (PI) and IMiDs may partly overcome the poor prognostic impact of some of them. In this study, we investigated a population-based consecutive cohort newly diagnosed patients with MM admitted during a defined time period to hospitals in Denmark, Norway, and Sweden. The impact of treatment modality on the prognostic importance of specific chromosomal aberration was investigated, with special ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…Furthermore, our findings suggest a poor outcome for patients with CKS1B amplification even with a PI or an IMiD-based induction in >90% of patients, and the use of post-transplant maintenance therapy in approximately 80% of patients. Similar outcomes were reported by Nahi et al, who found that patients with 1q21 gain had a shorter overall survival, which was not overcome by treatment with PI, IMiD or auto-HCT [33]. In contrast to induction, a higher proportion of patients in the CKS1B group received a PI-based maintenance (30% vs. 13%) than the control, and still had a shorter PFS and OS.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, our findings suggest a poor outcome for patients with CKS1B amplification even with a PI or an IMiD-based induction in >90% of patients, and the use of post-transplant maintenance therapy in approximately 80% of patients. Similar outcomes were reported by Nahi et al, who found that patients with 1q21 gain had a shorter overall survival, which was not overcome by treatment with PI, IMiD or auto-HCT [33]. In contrast to induction, a higher proportion of patients in the CKS1B group received a PI-based maintenance (30% vs. 13%) than the control, and still had a shorter PFS and OS.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the previously defined high-risk cytogenetic abnormalities, the 2016 International Myeloma Working Group consensus paper includes gain of 1q on FISH as a high-risk feature 10 ; this abnormality has also been shown to confer poor prognosis in other studies and analyses in MM 17,20,21 and has been suggested as 1 of the most important markers of poor prognosis with current treatments. 21 We therefore undertook a post hoc analysis of outcomes according to the presence of this abnormality, and incorporated patients with 1q21 amplification within the expanded high-risk group.…”
Section: Org Frommentioning
confidence: 99%
“…21 We therefore undertook a post hoc analysis of outcomes according to the presence of this abnormality, and incorporated patients with 1q21 amplification within the expanded high-risk group. As with the other high-risk subgroups and abnormalities, our findings showed a consistent PFS benefit with IRd vs placebo-Rd in patients with amp 1q21 alone (3% cutoff; HR, 0.781; 95% CI, 0.492-1.240) and in the expanded high-risk cytogenetics subgroup (HR, 0.664; 95% CI, 0.474-0.928).…”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…To date, outcome of MM patients carrying 1q21 gain remain poor, primarily due to failure to overcome drug resistance stemmed from this adverse CA 42, 43. To serve as a prognostic marker for this high‐risk subtype of MM, at least 3 criteria should be met, including that (1) it is often upregulated in MM and better increased with disease progression; (2) it must be amplified and/or overexpressed due to 1q21 gain; and (3) its expression must significantly correlate with poor prognosis of patients 44.…”
Section: Discussionmentioning
confidence: 99%